Persepsi Konsumen terhadap Kualitas Produk Cumi-cumi (Loigo sp) di Kota Bandung - Muhammad Zoelva Dyazhari Azriel; Junianto Junianto (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
Squid (Loligo sp.), which is high in protein, minerals, and omega-3 fatty acids, is one of the fisheries products that Indonesia, a coastal nation with abundant marine resources, has great potential to grow. Salted squid is a popular but less favored product because it is impractical, and squid processing is still subpar despite Bandung's growing demand. Although consumer views of food safety and quality are important when making purchases, issues with raw material quality, preservatives, and hygiene still exist. The purpose of this study is to determine the elements that influence Bandung consumers' opinions about the safety and quality of squid products. Direct observations, in-depth interviews, and focus groups with producers and customers were used to gather data using a qualitative methodology. The results show that consumers are quite interested in processed squid items, especially flavored ones, but they are also very concerned about safety and quality. Limited processing techniques and an inconsistent raw material supply make it difficult for producers to maintain consistent quality. The report emphasizes the need for better quality control, transparency in product information, and government support for supply chain management and standardization in order to close the gap between consumer expectations and producers' capabilities. Improved labeling, higher production standards, and legislative actions are among the suggestions made to support Bandung's squid processing sector. Improved labeling, higher production standards, and legislative actions are among the suggestions made to support Bandung's squid processing sector.